Entamoeba histolytica under Oxidative Stress: What Countermeasure Mechanisms Are in Place? - Pineda, Erika (Cells, 2017)
Entamoeba histolytica is the causative agent of human amoebiasis; it affects 50 million people worldwide and causes approximately 100,000 deaths per year. Entamoeba histolytica is an anaerobic parasite that is primarily found in the colon; however, for unknown reasons, it can become invasive, breaching the gut barrier and migrating toward the liver causing amoebic liver abscesses. During the invasive process, it must maintain intracellular hypoxia within the oxygenated human tissues and cellular homeostasis during the host immune defense attack when it is confronted with nitric oxide and reactive oxygen species. But how? This review will address the described and potential mechanisms available to counter the oxidative stress generated during invasion and the possible role that E. histolytica’s continuous endoplasmic reticulum (Eh-ER) plays during these events.